Confidence intervals, significance values, maximum likelihood estimates, etc. sharpened into Occam’s razors - Bickel, David R. (Université d'Ottawa | University of Ottawa, 2018)
Confidence sets, p values, and maximum likelihood estimates may be adjusted to favor sampling distributions that are simple compared to others in the parametric family. The adjustments are derived from a prior likelihood function previously used to adjust posterior distributions.
Keywords: confidence distribution; fiducial inference; Kolmogorov complexity; probability matching prior distribution